2015
DOI: 10.1039/c5ra17299c
|View full text |Cite
|
Sign up to set email alerts
|

Competitive lithium and sodium intercalation into sodium manganese phospho-olivine NaMnPO4 covered with carbon black

Abstract: The study demonstrates unusual capabilities of phospho-olivine NaMnPO4 to intercalate lithium and sodium reversibly, which makes it attractive electrode material instead of the conventional lithium analogue LiMnPO4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 45 publications
5
53
0
Order By: Relevance
“…To our knowledge there are no data about co‐intercalation of Na + and other metal ions (including Li + ) into olivine‐type NaFePO 4 . For olivine‐type NaMnPO 4 , however, a Li + /Na + co‐insertion has been verified based on electrochemical and ex‐situ diffraction, microscopic and spectroscopic techniques (Figure a,b) …”
Section: Structural Matrices Suitable For Li+ Na+ and Mg2+ Intercalamentioning
confidence: 98%
See 2 more Smart Citations
“…To our knowledge there are no data about co‐intercalation of Na + and other metal ions (including Li + ) into olivine‐type NaFePO 4 . For olivine‐type NaMnPO 4 , however, a Li + /Na + co‐insertion has been verified based on electrochemical and ex‐situ diffraction, microscopic and spectroscopic techniques (Figure a,b) …”
Section: Structural Matrices Suitable For Li+ Na+ and Mg2+ Intercalamentioning
confidence: 98%
“…It should be mentioned that till now, the electrochemical activity of a nanosized composite NaMnPO 4 /C has been only demonstrated by Boyadhzieva at al . It displays relatively good electrochemical activity when used as a cathode in model lithium ion cells: a specific capacity of 80–85 mAh g −1 can be retained for 15 cycles with a Columbic efficiency of 98 % . It has been also found that the NaMnPO 4 /C composite shows a chemical inertness after a prolonged soaking in the lithium electrolyte LiPF 6 /EC/DMC .…”
Section: Structural Matrices Suitable For Li+ Na+ and Mg2+ Intercalamentioning
confidence: 99%
See 1 more Smart Citation
“…[155] NaMnPO 4 /C composite was prepared through an ion-exchange reaction and ball milling processes. [156] The as-prepared compound consists of well-crystallized olivine-phase NaMnPO 4 with disordered carbon species and no antisite defects, delivering a reversible capacity between 80 and 85 mAh g −1 in model lithium cells (Figure 13b). Although the electrochemical performance is unsatisfactory, it is demonstrated that NaMnPO 4 is capable of reversibly intercalating both Na + and Li + ions based on the chemical reaction Li x Na 1−x MnPO 4 ↔ Li 0.0 Na 0.5 MnPO 4 (0.25 ≤x ≤ 0.45).…”
Section: Sodium Iron/manganese Phosphates and Iron/manganese Fluorophmentioning
confidence: 99%
“…Reproduced with permission. [156] Copyright 2015, Royal Society of Chemistry. c) Schematic illustration of Na + ion diffusion paths in Na 2 MnPO 4 F structure: (top left) possible paths with activation barrier lower than 650 meV, and in the b direction through the (top right) Na1-Na4 chain, (bottom left) Na2-Na3 chain, and (bottom right) interchain diffusion; and d) charge/discharge profiles of the first three cycles of Na 2 MnPO 4 F at a current density of 10 mA g −1 .…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%